2010
DOI: 10.1080/01488376.2010.493845
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Students about Younger and Older Men and Women who May Be Homeless

Abstract: Future human service providers will interact with homeless persons in health, mental health, and social service practice contexts. This study investigated the perceptions of students enrolled in social work courses who are pursuing degrees in human service programs toward older and younger female and male homeless individuals. Respondents (N = 207) were given one of four vignettes in which a character was identified as an older male, a younger male, an older female, or a younger female who was frequently seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Having an itchy head or contact with an infected individual also signified an active infestation of head lice . Social characteristic traits linked to head lice include perceptions of poor hygiene, unkemptness, lower socioeconomic class, less education, non‐White ethnicity, or homelessness . Schools and community organizations mark individuals by excluding them from activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having an itchy head or contact with an infected individual also signified an active infestation of head lice . Social characteristic traits linked to head lice include perceptions of poor hygiene, unkemptness, lower socioeconomic class, less education, non‐White ethnicity, or homelessness . Schools and community organizations mark individuals by excluding them from activities.…”
Section: Resultsmentioning
confidence: 99%
“…Although the perception is inaccurate, head lice have been associated with uncleanliness, homelessness, poverty, and lower education . These negative perceptions foster fear, enable disproportionate responses and drive policy and treatment practices.…”
Section: Introductionmentioning
confidence: 99%
“…Noel and Westby suggested that this negative self‐understanding is reinforced in prison and by the societal narratives offenders encounter when reentering society and the workforce. Similarly, in a study of social work students' perceptions of homeless individuals, Kane, Green, and Jacobs () found that, when presented with a vignette of homeless individuals, most respondents viewed the individuals as substance abusers, mentally ill, resistant to assistance, and dirty. More recently, Kane, Green, and Jacobs () surveyed social work students and found that they perceived homeless older adults to be lonely, abandoned by their families, and living in fear.…”
Section: The Power Of Narratives: Personal Cultural and Societal Inmentioning
confidence: 99%
“…People most often think of the homeless as older men, perhaps military veterans and those struggling with mental health issues and substance abuse. Homeless women are believed to be old and unable to afford housing (Kane et al. , 2010).…”
Section: Homelessness In the Hee Frameworkmentioning
confidence: 99%
“…People most often think of the homeless as older men, perhaps military veterans and those struggling with mental health issues and substance abuse. Homeless women are believed to be old and unable to afford housing (Kane et al, 2010). Nichols et al (2018) add another dimension, in that there is also a homeless prototype: older men, young people and abused women.…”
Section: Belief Systemsmentioning
confidence: 99%